Polyploidy in haloarchaea: advantages for growth and survival - Zerulla, Karolin; Soppa, Jörg (Frontiers in Microbiology, 2014)
The investigated haloarchaeal species, Halobacterium salinarum, Haloferax mediterranii, and H. volcanii, have all been shown to be polyploid. They contain several replicons that have independent copy number regulation, and most have a higher copy number during exponential growth phase than stationary phase. The possible evolutionary advantages of polyploidy for haloarchaea, most of which have experimental support for at least one species, are discussed. These advantages include a low mutation rate and high resistance towards X-ray irradiation and desiccation, which depend on homologous recombination. For H. volcanii, it has been shown that gene conversion operates in the absence of selection, which leads to the equalization of genome copies. On the other hand, selective forces might lead to heterozygous cells, which have been verified in the laboratory. Additional advantages of polyploidy are survival over geological times in halite deposits as well as at extreme conditions on earth and at simulated Mars conditions. Recently, it was found that H. volcanii uses genomic DNA as genetic material and as a storage polymer for phosphate. In the absence of phosphate, H. volcanii dramatically decreases its genome copy number, thereby enabling cell multiplication, but diminishing the genetic advantages of polyploidy. Stable storage of phosphate is proposed as an alternative driving force for the emergence of DNA in early evolution. Several additional potential advantages of polyploidy are discussed that have not been addressed experimentally for haloarchaea. An outlook summarizes selected current trends and possible future developments.